Association Between Inflammatory Bowel Disease and Spondyloarthritis: Findings from a Nationwide Study in Sweden. (5th May 2022) - Shrestha, Sarita; Brand, Judith S; Järås, Jacob; Schoultz, Ida; Montgomery, Scott; Askling, Johan; Ludvigsson, Jonas F; Olen, Ola; Halfvarson, Jonas; ,
Abstract: Background and Aims: Inflammatory bowel disease [IBD] has been associated with spondyloarthritis [SpA], but population-based estimates are scarce. Here we compare the occurrence of SpA before and after a diagnosis of IBD with the general population, overall and by IBD subtype and age. Methods: We used a nationwide register-based cohort study of 39 203 patients diagnosed with IBD during 2006-2016, identified from Swedish registers and gastrointestinal biopsy data, and 390 490 matched reference individuals from the general population. Conditional logistic regression models were used to estimate odds ratios [ORs] for a prior [prevalent] SpA diagnosis and conditional Cox regression to calculate hazard ratios [HRs] for a subsequent [incident] SpA diagnosis in IBD patients. Results: IBD patients were more likely to have prevalent SpA at IBD diagnosis [2.5%] compared with reference individuals [0.7%] with an OR of 3.48 [95% CI: 3.23, 3.75]. They also more often received an incident diagnosis of SpA; during 23 341 934 person-years of follow-up in IBD patients, there were 1030 SpA events [5.0/1000 person-years] compared with 1524 SpA events in the reference group [0.72/1000 person-years], corresponding to an HR of 7.15 [95% CI: 6.60, 7.75]. In subgroup analyses, associations were most pronounced among patients with Crohn's disease ([OR = 5.20; 95% CI: 4.59, 5.89], and [HR = 10.55; 95% CI: 9.16, 12.15]) and paediatric onset IBD ([OR = 3.63; 95% CI: 2.35, 5.59] and [HR = 15.03; 95% CI: 11.01, 20.53]). Conclusions: IBD patients more frequently experience SpA both before and after the diagnosis of IBD compared with the general population, supporting evidence of a shared pathophysiology. The variation in SpA comorbidity, across IBD subtypes and age groups, calls for targeted approaches to facilitate timely diagnosis and intervention. Graphical Abstract: